Physicochemical, Functional, and Nutraceutical Properties of Eggplant Flours Obtained by Different Drying Methods - Rodríguez Jiménez, Jenny Rosa Elvira; Amaya Guerra, Carlos Abel; Báez González, Juan Gabriel; Aguilera González, Carlos Javier; Urías Orona, Vania; Niño Medina, Guillermo (2018)
The importance of consuming functional foods has led the food industry to look for alternative sources of ingredients of natural origin. Eggplants are a type of vegetable that is valued for its content in phytochemical compounds and it is due to the fact that this research is conducted towards the development of eggplant ﬂour as a proposal to be used as a functional ingredient in the food industry. In this study, the eggplant fruits were divided into four groups, based on the drying method and the equipment used: Minced, drying oven (T1); sliced, drying oven (T2); sliced and frozen, drying tunnel (T3); and sliced, drying tunnel (T4). All the eggplant ﬂours showed the same trend regarding their antioxidant capacity and phenolic content in the order T2 > T4 > T1 > T3.The freezing of egg plant was found to have a negative effect on functional and antioxidant properties. With respect to their nutritional composition, the ﬂours did not change in their crude ﬁber, protein, and fat contents. In general terms, the T2 ﬂour is a potential ingredient for the preparation of foods with functional properties since it is rich in phenolic compounds and antioxidants.